An optimization planning method for rural distribution systems considering on-load tap changers and energy storage - Yang, Xin; Zhong, Yalin; Zhou, Fan; Xu, Ran; Jiao, Fei; Xu, Jun (Frontiers in Energy Research, 2025)
Under the guidance of the “dual carbon” target, rural distribution systems are increasingly affected by power fluctuations and voltage violations owing to the growing penetration of distributed photovoltaic (PV) generation. To address these issues, we propose an optimization planning method for rural distribution systems by considering on-load tap changers (OLTCs), energy storage systems (ESSs), and auxiliary flexible interconnection devices such as soft open points (SOPs). Accordingly, we developed a two-level optimization model: the upper level minimizes the total planning and operational costs by determining the optimal deployment of OLTCs and ESSs under technical and economic constraints; the lower level evaluates the system reliability by calculating the expected energy not supplied (EENS) based on the fault impact matrix (FIM) while ensuring network connectivity and exclusive transfer paths. We also propose an iterative strategy to solve the two-level optimization model, where the planning decisions of the upper level and reliability evaluation solutions of the lower level interact until the convergence condition is satisfied. The framework of the iterative strategy was implemented in the AMPL modeling tool along with the Gurobi solver to ensure computational efficiency. The simulation results indicate that the proposed method achieves 100% PV accommodation, reduces the EENS by over 50%, and reduces the power system costs by approximately 16%, thereby improving both the economic performance and reliability effectively.